Improved immobilization and stabilization of lipase from Rhizomucor miehei on octyl-glyoxyl agarose beads by using CaCl2. Issue 1 (January 2016) - Fernandez-Lopez, Laura; Rueda, Nazzoly; Bartolome-Cabrero, Rocio; Rodriguez, Maria D.; Albuquerque, Tiago L.; dos Santos, Jose C.S.; Barbosa, Oveimar; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: CaCl2 remained soluble at pH 10 in Gly buffer. CaCl2 stabilized OC-RML but nor OC-CRL at pH 10. OCGLX-RML prepared in presence of CaCl2 exhibited improved activity and stability. CaCl2 and MnCl2 stabilized also OCGLX-RML biocatalysts. OC-X-RML are also stabilized by CaCl2 in solvent inactivations. Abstract: A strategy to stabilize octyl (OC)- Rhizomucor miehei lipase (RML) and OC- Candida rugosa lipase (CRL) at pH 10 is necessary to take full advantage of the immobilization of these enzymes on OC-glyoxyl (OCGLX) supports. CaCl2 and MnCl2 have been reported to stabilize OC-RM and OC-CRL at pH 5.0 and 7.0. After screening different buffers, 5 mM CaCl2 was found to be fully soluble in Gly at pH 10. OC-RML was 15 folds stabilized at this pH value by CaCl2, while OC-CRL was not. This salt was used in the preparation of octyl-glyoxyl (OCGLX)-RML, permitting to maintain almost unaltered the OC-RML activity that was 3 fold higher than that of the free. This preparation was 30% and 3 folds more stable in thermal or acetonitrile inactivations respectively than the standard OCGLX one. The stabilizing effect of CaCl2 and MnCl2 on the OCGLX preparations was studied. These salts stabilized both OCGLX-RML preparations, although the one prepared using Ca 2+ during the covalent attachment was more stabilized than the standard one by the presence of Ca 2+, even 7-8 folds in the presence of aceonitrile. Thus, this additive permits to recover an OCGLX-RML preparation more stable and active than the standard protocol.